Ségrégations résidentielles et construction de parcours de formation - Emmanuelle Leclercq (Développement Durable et Territoires)
This article suggests marking certain theoretical approaches concerning the disparities of the chances. According to the disciplinary membership within the social sciences, to see especially social prevalencia the approaches where the question of the territory is often slanted. We shall analyze the means of the knowledge of this reality of the disparities of the chances compared to territories, the means of the statistical production, by the approaches of the Cereq.We shall show how this question of the choices of route and fight against the defeat is approached on the scale of a university, by taking the example of certain initiatives realized notably in Champagne Ardenne so showing the complexity of an objective knowledge.